Obstacles to Agricultural Development in the District of Samarra and AL-Dour : Hambatan Pembangunan Pertanian di Wilayah Samarra dan Al-Dour - Zilal Abdul Karim Muhamad; Abdul Karim Rashid Abdul Latif (Academia Open, 2023)
This article presents a comprehensive study conducted in Samarra and Al-Dour districts, focusing on the impact of agricultural components on development. The study aims to identify and analyze the natural, human, and economic obstacles that impede agricultural progress in the region. Through questionnaire data analysis, several key findings emerge. Natural factors such as inadequate rainfall, arid soil conditions, and soil salinization pose significant challenges to agricultural development. Insufficient utilization of water resources further exacerbates these constraints. Agricultural pests also cause substantial damage to crops, leading to farmer abandonment of agricultural practices. Roughly 30-35% of cultivated areas are affected. Moreover, a decline in agricultural labor is observed, with individuals deterred by constraints and limited financial returns. The increasing population in the region intensifies food demand and pressures agricultural land for housing, compounding challenges for farmers. Water scarcity emerges as a primary constraint, leading to neglect of agricultural areas due to inadequate irrigation. Progressive soil salinization and desertification, influenced by natural and human factors, worsen the situation. Approximately 22.38 km² of land are affected, particularly in eastern and southern Samarra and eastern Al-Dour. The study underscores the need for targeted interventions and policies to overcome these obstacles and foster sustainable agricultural development. Strategies should prioritize water resource management, pest control, technological advancements, and addressing labor shortages. Implementing these measures will contribute to long-term agricultural sustainability, food security, and economic growth in the studied regions. Highlights: Natural and human constraints hinder agricultural progress in Samarra and Al-Dour districts. Agricultural pests cause significant damage and discourage farming activities. Water scarcity and soil salinization negatively impact agricultural development.